Impression Flow Based on Comment in Islamic Studies from Instagram using Sentiment Analysis - Mariyatul Norhidayati; Munsyi M.T (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Islamic studies in industrial revolution 4.0 grown very rapidly. Everyone can access an information everywhere and everytime using their end devises such a smartphone and laptop base on internet access using a social media such instagram, facebook, and twitter. development of da'wah media that is not only through radio television and through studies conducted either in mosques or other places for delivering of studies and insights about Islam for all muslims in Indonesian country especially in Kalimantan Selatan. One of aplication social media for studying islam is Instagram. All of preachers is very easily make a post on Instagram for sharing a religious knowledge to users of Instagram social media, hence this case a lot of Islamic da'wah accounts in great demand by the muslims people in Indonesia. Islamic posts made by preachers on Instagram make a lot of conflict and the direction of negative or positive impressions left by users through the comments column provided from instagram. To determine the positive and negative directions of the post from a preacher. We develop a system for detecting the direction of impression from all of comment on Islamic content on Instagram created by the user using a sentimen analysis. This system analyzes comments left on a post from a preacher's Instagram story. The system that was built succeeded for classifying the filtered comments by attributing the direction of the da'wah impression posted by the preacher. The classification of the impression direction of this system contains 3 impression directions, namely positive, negative, and neutral